Unreasonable minds and imperfect self-defense. (May 2022) - Erickson, Steven K.
Abstract: Western legal systems recognize the right to self-defense as a right of individuals, under certain circumstances, to use physical force to defend themselves from an aggressor. This right requires an honest and reasonable belief of the person asserting it regarding the circumstances in which force is used. Some jurisdictions also permit a defense of imperfect self-defense, allowing for reduced culpability for the crime of homicide if a person's beliefs are honest but unreasonable. If the unreasonable belief is based on a mental illness, however, the defense is disallowed in every jurisdiction in the United States. This development relies upon an untenable position that false beliefs produced by mental disorders should be excluded based on erroneous assumptions about psychotic illness. This article argues that the current precedent is incoherent with the core structure of criminal responsibility and in tension with current scientific understandings and should change to do justice.